Numerical and experimental investigation of crack in beams using frequency contour method - S, Nancy Debora; I, Antony Godwin; R, Irish Nivitha; L, Rishipal Reddy (International Journal of Engineering and Technology, 2018)
Health monitoring of Structures is a vital tool for engineers to ensure the life of important structures like Dams and bridges, Stadiums and buildings and, Platforms and vessels, Wind turbines Airframes, and large machinery and equipments. SHM helps to detect damage at earlier stage before failure occurs by sensing systems. Various damage detection methods are available in accordance with vibrational characteristics of the structure. In this paper Frequency contour method which consumes less time is employed to detect, locate, and characterize damage in structural and mechanical systems. Experimental and Numerical modal analysis were carried out on cracked and healthy beams of steel with cantilever support conditions of size 20mmx20mm and of length 300mm using ABAQUS. Three natural frequencies are obtained as a basic criterion for crack detection. To locate the damage of the normalized frequency in terms of location and depth of the crack were designed using MATLAB. The intersection of three contour lines represents crack location and crack depth. Prediction of damage using frequency contour method gives good result.